2021
DOI: 10.1111/ajt.16206
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of African American adults about the use of apolipoprotein L1 (ApoL1) genetic testing in living kidney donation and transplantation

Abstract: Apolipoprotein L1 (ApoL1) predictive genetic testing for kidney disease, and its emerging role in transplantation, remains controversial as it may exacerbate underlying disparities among African Americans (AAs) at increased risk. We conducted an online simulation among AAs (N = 585) about interest in ApoL1 testing and its cofactors, under 2 scenarios: as a potential living donor (PLD), and as a patient awaiting transplantation. Most respondents (61%) expressed high interest in genetic testing as a PLD: age ≥35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 55 publications
3
33
0
Order By: Relevance
“…Limitations of this study include that the survey was conducted at one academic center, and the survey did not undergo independent validationalthough we employed an iterative process in developing it. In addition, the questions posed with regards to living donation were hypothetical in nature, similar to a recent study about APOL1 testing in transplantation by Berrigan et al 22 Although, more than half of participants in our study both had an affected first-degree relative with kidney disease and had considered living donation, making them more likely to face APOL1 testing as part of a clinical evaluation, compared to community dwelling participants in their study. Finally, while some would suggest the use of a correction for multiple hypothesis testing, we have chosen not to do so in our analysis given the limited number of hypotheses being tested and to avoid inflating the risk of a type II error among other considerations.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Limitations of this study include that the survey was conducted at one academic center, and the survey did not undergo independent validationalthough we employed an iterative process in developing it. In addition, the questions posed with regards to living donation were hypothetical in nature, similar to a recent study about APOL1 testing in transplantation by Berrigan et al 22 Although, more than half of participants in our study both had an affected first-degree relative with kidney disease and had considered living donation, making them more likely to face APOL1 testing as part of a clinical evaluation, compared to community dwelling participants in their study. Finally, while some would suggest the use of a correction for multiple hypothesis testing, we have chosen not to do so in our analysis given the limited number of hypotheses being tested and to avoid inflating the risk of a type II error among other considerations.…”
Section: Discussionsupporting
confidence: 59%
“…Beyond the potential prognostic value of knowing living donors' APOL1 genotype, there is a growing desire for individuals from Black communities to know about their risk for APOL1-mediated kidney disease. [21][22][23][24][25] What remains unclear, however, is whether knowing more about APOL1, including the potential benefits and drawbacks associated with APOL1 testing, influence interest in testing among prospective living donors. In this study, we assessed views on APOL1 testing in the context of living kidney donation among individuals recruited from a nephrology clinic waiting room, before and after presenting them with APOL1 related education, including the potential benefits (e.g., knowledge of personal risk, etc.)…”
mentioning
confidence: 99%
“…12 Here, we have sought to provide clinicians with tools to help them to address this call for more widespread APOL1 testing. The experts agreed that awareness of APOL1-associated nephropathy is low among the Black community and key decision makers, as noted in several studies, 12,43,44,48 and this is not surprising given that there have been no major educational initiatives in this area. The panel agreed on various factors that may contribute to this lack of awareness and that this may reinforce a lack of trust among Black people in the medical establishment.…”
Section: Discussionmentioning
confidence: 85%
“…Other studies have found that in the context of kidney transplantation, community views regarding APOL1 testing are complex (Berrigan et al, 2021; Gordon et al, 2018). A study of African Americans who have donated a kidney reported an interest in knowing their APOL1 status, but most would have donated even if they knew they had the risk genotype.…”
Section: Discussionmentioning
confidence: 99%